The once‐daily human GLP‐1 analogue liraglutide impacts appetite and energy intake in patients with type 2 diabetes after short‐term treatment. Issue 10 (23rd April 2013) - Flint, A.; Kapitza, C.; Zdravkovic, M.
Abstract : The aim was to investigate effects of liraglutide on appetite and energy intake in a randomized, placebo‐controlled, double‐blind, crossover study. Eighteen subjects with type 2 diabetes were assigned to treatment with once‐daily subcutaneous liraglutide (increasing by weekly 0.6 mg increments) or placebo for 3 weeks. Appetite ratings were assessed using visual analogue scales during a 5‐h meal test. Energy and macronutrient intake during the subsequent ad libitum lunch were also measured. After 3 weeks, mean postprandial and minimum hunger ratings were significantly lower with liraglutide 1.8 mg than placebo (p < 0.01), and the mean overall appetite score was significantly higher (p = 0.05), indicating reduced appetite. Liraglutide was associated with higher maximum fullness ratings (p = 0.001) and lower minimum ratings of prospective food consumption (p = 0.01). Mean estimated energy intake was 18% lower for liraglutide than placebo [estimated ratio 0.82 (95% CI 0.73;0.94); p = 0.004], but no significant differences in macronutrient distribution were noted. Findings suggest that reduced appetite and energy intake may contribute to liraglutide‐induced weight loss.